2012
DOI: 10.6002/ect.2010.0127
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four Hour Steroid Avoidance Immunosuppressive Regimen in Liver Transplant Recipients

Abstract: Objectives: To investigate the efficacy and safety of an immunosuppressive regimen of steroid avoidance in combination with induction therapy and tacrolimus in liver transplant recipients. Materials and Methods: Eighty-two adult liver transplant recipients were randomized into 2 groups: standard protocol group (n=41) in which steroids were withdrawn 3 months after the operation, and a 24-hour steroid avoidance group (n=41) in which steroids were eliminated within 24-hours. The incidence of acute rejections, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…[18][19] The present study also confirmed that discontinuing steroids early after liver transplant is a safe and effective immunosuppression strategy without increasing the frequency of acute rejection. [20][21][22][23] In the present study, we used basiliximab induction and a steroid-sparing immunosuppressive regimen (mycophenolate mofetil and tacrolimus), which was associated with a low incidence of acute rejection; only 1 of 23 patients had acute rejection, similar to that previously reported, and this was reversed by large doses of steroid therapy. 24 In the present study, 2 patients died of perioperative pulmonary infection, and 3 patients died of tumor recurrence.…”
Section: Discussionsupporting
confidence: 55%
“…[18][19] The present study also confirmed that discontinuing steroids early after liver transplant is a safe and effective immunosuppression strategy without increasing the frequency of acute rejection. [20][21][22][23] In the present study, we used basiliximab induction and a steroid-sparing immunosuppressive regimen (mycophenolate mofetil and tacrolimus), which was associated with a low incidence of acute rejection; only 1 of 23 patients had acute rejection, similar to that previously reported, and this was reversed by large doses of steroid therapy. 24 In the present study, 2 patients died of perioperative pulmonary infection, and 3 patients died of tumor recurrence.…”
Section: Discussionsupporting
confidence: 55%
“…These drugs have been in long use, and their benefit in prevention of graft rejection in OLT is well‐established. Their safety has also been proven . However, immunosuppressants, by definition, cause numerous side effects with gastrointestinal symptoms, deterioration of kidney function, arterial hypertension, diabetes, and osteoporosis .…”
mentioning
confidence: 99%
“…No differences were found in the incidence of hypertension and hyperlipidemia between the steroid early avoidance and standard groups. 19 In another study, the incidence of hypertension, hyperglycemia, and DM were significant lower in steroid-free recipients, 20 demonstrating that the effect of steroids on metabolic complications are still controversial.…”
Section: Discussionmentioning
confidence: 98%